Saving Children, Controlling Families: Punishment, Redistribution, and Child Protection. (June 2016) - Edwards, Frank
This study shows that state efforts at child protection are structured by the policy regimes in which they are enmeshed. Using administrative data on child protection, criminal justice, and social welfare interventions, I show that children are separated from their families and placed into foster care far more frequently in states with extensive and punitive criminal justice systems than in states with broad and generous welfare programs. However, large welfare bureaucracies interact with welfare program enrollment to create opportunities for the surveillance of families, suggesting that extensive and administratively complex welfare states engage in "soft" social control through the surveillance and regulation of family behavior. The article further shows that institutionalization, a particularly restrictive form of foster care placement, is least common in states with broad and generous welfare regimes and generally more common under punitive regimes. Taken together, these findings show that policy regimes influence the interaction between families and the state through their proximate effects on family structure and well-being and through institutional effects that delimit the routines and scripts through which policymakers and street-level bureaucrats intervene to protect children.